(untitled) (Research, Society and Development, 2020)
Identify in the literature the scientific evidence about of context breastfeeding in the first hour of life. Integrative bibliographic research, carried out from March to June 2019 with search for data from the Virtual Health Library, in the Lilacs, Medline and Cochrane do Brasil databases, using the term ’breastfeeding’ and keywords ’first hour of life’. 19 articles were selected (2 Cochrane, 1 Medline and 16 Lilacs). It was evident that women who had skin-to-skin contact in the first hour of life are more likely to breastfeed. And the professionals of the health services reported that the performance of normal birth has helped in the practice of breastfeeding in the first hour of life. Based on the selected articles, it was observed the importance of the 4th step of the Baby Friendly Hospital Initiative and how the commitment of health professionals and institutions is necessary. To this end, comprehensive assistance to women and their families is reinforced, starting with prenatal care, continuing at the time of birth, with support from the companion.